(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف البحث إلى الوقوف على رأي رسل في أسباب قيام الحروب والدوافع التي تقود البشر إلى إذكاء نار التعصب وكره الآخر , الأمر الذي سيدفع بالضرورة إلى الحرب عليه وقتاله ، وهو مايعني التعدّي على حياته وحقه في الوجود الذي هو حق طبيعي ومكتسب لكل إنسان . وقد رفض "رسل" بهذا السياق الحروب ودعى إلى نبذها , لأنه رأى فيها أسباباً ظالمة تمنع البشر من أن يلتقوا على صعد المحبة والإنسانية . كذلك اعتبر أن الفقر إضافة إلى الحرب قد تكون من بين الأسباب الرئيسية التي تسلُب البشر حياتهم وتهدد وجودهم The aim of this article is to investigate Russell’s view which account for the deep reasons of wars and disputes between the states and nations. Also, we will try to signify the veiled motives which lead the human beings to hate, assault and aggress each others. This means, we will try to present the reasons which make the human beings, according to Russell- violate the life and the natural existence of others. Also, we will try to examine the reasons and motives of war in their relations with the concept of power, because, according to Russell, if this concept avails in the hands of any state, it will be the sufficient reason to wage war against any other state. These kinds of wars are considered by Russell as unjust wars that seek to occupy the land and properties of others.